Analysis of archaeological sampling methods using the complete surface data from the Pirque Alto Site in Cochabamba, Bolivia - Green, Liz (Archaeological Studies Program, University of Wisconsin-La Crosse, 2007)
Sampling is an extremely important aspect of archaeological fieldwork, and it can significantly influence interpretation; therefore, the effects of these processes must be understood and controlled. Various experimental sampling methods are tested against the surface recovery data collected from the Pirque Alto site in Cochabamba, Bolivia. The project addresses the following questions: do results from the sampling methods reflect the total surface recovery; what method gives the most accurate results for this site and why; and at what percentage of quadrat (unit) samples taken per method do the results show validity. Finally, in what way are the methods biased and how can these biases be addressed? The project has yielded information about how various methods would or would not have affected the interpretation of the Pirque Alto site, and the results were thn applied to a broader study and understanding of sampling methods.
Keywords: Archaeology -- Statistical methods; Cochabamba Valley (Bolivia) -- Antiquities; Archaeology -- Methodology